IMPLEMENTASI PERBAIKAN UI/UX SPANDUK IKLAN PADA VIDEO PLAYER DENGAN METODOLOGI AGILE DI PT X - Febryan, Claudio; Setiawati, Ni Luh Putu Lilis Sinta (LPPM Universitas Bina Bangsa, 2024)
The development of streaming services is rapidly growing in Indonesia. One of the companies in the streaming service sector is PT X, which has an application rating of 4.1. In the application development, one of the features is advertising provision while users are using the application or watching. There are several complaints from users whose data is stored through app logs from January onwards. The main issues related to advertising are duplicate content during watching and design development. These issues were then addressed and improved using the agile method by conducting continuous iterations based on user feedback. The research resulted in the improvement of the user interface design in overlay ads by changing the position and size of the dismiss button, and the development of user experience for duplicate content by prioritizing and changing the logic when displaying ads. Based on the implementation results, it was found that the improvements and developments in advertising decreased user complaints by 30% and increased user satisfaction during watching